Effectiveness of Telecardiology Interventions on Reducing Hospital Readmissions in Elderly Heart Failure: Systematic Review and Meta-Analysis - Virk, Ghazala S.; Hack, Sarah; Gundala, Chandini; Saeed, Tanzeela; Pate, Deep; Varakala, Sai Prashanthi; Karki, Yukesh; Ugripelli, Venkata Avinash; Abid, Marium; Essani, Binish; et al. (Cardiology and Cardiovascular Medicine, 2025)
Heart failure becomes a chronic condition when the heart cannot pump blood properly. The cycle then repeats, hospitalizations are recorded for acute heart failure; interventions are sought to prevent further hospitalizations. Telecardiology interventions, such as remote monitoring and teleconsultation, were therefore proposed as a means to ramp up heart failure management and diminish the incidence of readmission. The systematic review and meta-analysis aimed to evaluate the impact of telecardiology interventions on two levels of outcome-reduction of hospital readmissions. An elaborate search was carried out in renowned bibliographic databases, namely, PubMed, Google Scholar, Cochrane Library, and Scopus, for randomized controlled trials (RCTs) and cohort studies published between 2000 and 2025. The included studies evaluated telemedicine interventions, which included mobile health applications, nurse-led telemonitoring, and teleconsultations. The primary outcome was the rate of hospital readmission; the secondary outcome measures included quality of life, patient satisfaction, and functional capacity. Meta-analysis on pooled data was done using a random-effects model for effect size estimation. Overall effect size was found to be 0.71 (95% CI: 0.31-1.11). It suggested a moderate reduction in readmissions with telecardiology interventions, though high heterogeneity (I² = 91.95%) was seen, which is due to differences in the designs of included studies, interventions, and populations. There was no significant publication bias as measured by the funnel plot and Egger's test. Risk of Bias showed variability across studies; some were low risk, and others moderate to high risk. Despite these limitations, results indicate that telecardiology may be effective in reducing hospital readmissions, although future research will be needed to better refine intervention models and patient-specific approaches.